Destabilized green fluorescent protein detects rapid removal of transcription blocks after genotoxic exposure. (August 2007) - Kitsera, Nataliya; Khobta, Andriy; Epe, Bernd
High stabilities of reporter proteins and their messenger RNAs (mRNAs) interfere with the detection of rapid transient changes in gene expression, such as transcriptional blocks posed by genotoxic DNA lesions. We have modified a green fluorescent protein (GFP) gene within the episomal pMARS vector by addition of a fragment encoding for mouse ornithine decarboxylase (ODC) proline-glutamate-serine-threonine-rich (PEST) sequence in order to target the protein to the proteasomes and achieved an unprecedentedly fast GFP turnover in permanently transfected human cells. As early as 1 h after inhibition of protein synthesis by cycloheximide, the number of fluorescent cells decreased more than 5-fold. Concordantly, treatments with transcription inhibitors α-amanitin and 5, 6-dichloro-1-β-D-ribofuranosylbenzimidazole (DRB) resulted in progressive depletion of the destabilized GFP, detected as fluorescence decline, while the stable protein levels were not affected under the same conditions. Moreover, fluorescence of the destabilized but not of normal GFP decreased strongly and in a dose-dependent manner following an instant transcription block induced by ultraviolet-C (UVC) irradiation. In agreement with the transient nature of the transcriptional block due to transcription-coupled DNA repair, the GFP fluorescence fully recovered after several hours.